2018
DOI: 10.1002/ldr.3194
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of mixed tree stands in restoration of upper soil layers on postmining sites: A five‐year leaf litter decomposition experiment

Abstract: No in‐depth studies covering litter decomposition were previously conducted on afforested postmining sites despite the importance of litter decomposition on soil formation, especially in degraded areas. We aimed to compare leaf litter decomposition rates of 14 tree species growing in mixed stands on a postmining spoil heap, and to compare their decay rates with those obtained in pure stands of tree species that are very often planted in postmining areas. The study was conducted on the Bełchatów Lignite Mine sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 56 publications
1
37
1
Order By: Relevance
“…500 m from our study site). Our results are also partly in line with Horodecki and Jagodziński [49] and Horodecki et al [28], who recorded lower decomposition rates for litter of F. sylvatica and Q. rubra in Scots pine stands, but higher rates in mixed stands. Studies on Quercus prinus litter demonstrated that the leaves 'disappeared' slowly and that there was minimal faunal influence on decomposition rates [50].…”
Section: Discussionsupporting
confidence: 92%
“…500 m from our study site). Our results are also partly in line with Horodecki and Jagodziński [49] and Horodecki et al [28], who recorded lower decomposition rates for litter of F. sylvatica and Q. rubra in Scots pine stands, but higher rates in mixed stands. Studies on Quercus prinus litter demonstrated that the leaves 'disappeared' slowly and that there was minimal faunal influence on decomposition rates [50].…”
Section: Discussionsupporting
confidence: 92%
“…They also revealed that litter structure might affect litter microclimate, and they also showed significant differences in microarthropod assemblages depending on litter type and whether the litter was single-or mixed-species. Likewise, the fact that in our experiment the oak litter was significantly different from other leaf types might be explained by its different lignin content [64] or a different decomposition rate, which depends on lignin content, as well as microand macroelements [36,54]. According to Osler et al [65] decomposition rate is strongly correlated with microarthropod assemblages, however, only after 20% litter mass loss of the initial weight.…”
Section: Discussionmentioning
confidence: 48%
“…After extraction of soil invertebrates (see paragraph 2.2. ), in order to determine the rate of decomposition, leaves were dried at 65 • C to obtain a constant dry mass, then the mass loss was determined in relation to the initial litter mass in every litterbag [54].…”
Section: Site Description and Experimental Designmentioning
confidence: 99%
“…In recent years, an increasing number of studies have focused on changes in the decomposition rates of litter composed of a mixture from different species that often exist in nature (Horodecki, Nowiński, & Jagodziński, 2018;Li, Cui, & Yang, 2012;Montané, Romanyà, Rovira, & Casals, 2013;Tan et al, 2013). The results showed that the decomposition characteristics of mixed litter from different species are distinguishable from those of single-species litter.…”
mentioning
confidence: 99%